Economic accounting and development planning : an introduction to general principles of accounting, input-output analysis, and national income accounts and their application to planning economic development - Van Arkadie, Brian; Frank, Charles Raphael (New York : Oxford University Press, 1966)
This edition was motivated by a desire to adapt the first edition to a different class of readers. The first edition, has been modified to include additional applications of economic accounting techniques and applications over a wider range of geographical areas.
"The original work is part of the Series of undergraduate teaching works in economics being developed at Makerere College, University of East Africa, with the assistance of the Rockefeller Foundation."
Includes bibliographical references and index.
ne 26/08/2019
Loans
Keywords: Accounting; Input-output analysis; National income; Economic policy